The Analisis SWOT Untuk Meningkatkan Potensi Jaring Dahlia Hj Fatimah Sebagai Tempat Wisata Kuliner Legenda di Banjarmasin Kalimantan Selatan - Risanta, Muhammad; Diany, Adista Anjar (Jurnal Penelitian Ilmiah INTAJ, 2025)
Jaring Dahlia Hj Fatimah is one of the culinary legends of Banjarmasin City. The main menu of this culinary specialty is processed Jengkol with tahilala or boiled coconut milk sediment, petah, and various other processed jengkol. This research aims to analyze the potential of Jaring Dahlia Hj Fatimah as a culinary tourism attraction so that it can be widely known by people from various regions to maintain a family business that has been running since 1987. The research method used is descriptive qualitative using SWOT analysis with research sources namely the owner, employees, and customers of Jaring Dahlia Hj Fatimah in Banjarmasin. The results showed that there are strategies that can be carried out by Jaring Dahlia Hj Fatimah by utilizing existing strengths and opportunities and minimizing existing weaknesses and threats. This research also indicates that a family business that has been established since 1987 such as Jaring Dahlia Hj Fatimah certainly also has weaknesses and will continue to face threats around such as the emergence of competition and street food that is rampant in the community. A digital marketing strategy is needed to be able to maintain business existence and introduce culinary to today's younger generation.